Antioxidant Enzyme Activity and mRNA Expression in Reproductive Tract of Adult Male European Bison (Bison bonasus, Linnaeus 1758). Issue 1 (28th March 2012) - Koziorowska‐Gilun, M; Gilun, P; Fraser, L; Koziorowski, M; Kordan, W; Stefanczyk‐Krzymowska, S
Contents: Antioxidants in the male reproductive tract are the main defence factors against oxidative stress caused by reactive oxygen species production, which compromises sperm function and male fertility. This study was designed to determine the activity of antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx), in the testicular and epididymidal tissues of adult male European bison ( Bison bonasus ). The reproductive tract tissues were subjected to real‐time reverse transcriptase–polymerase chain reaction (RT‐PCR) analysis to quantify mRNA expression levels of five antioxidant enzymes: copper/zinc SOD (Cu/Zn SOD), secretory extracellular SOD (Ec‐SOD), CAT, phospholipid hydroperoxide glutathione peroxidase (PHGPx) and GPx5. The corpus and cauda epididymidal tissues displayed greater (p < 0.05) SOD activity compared with the testicular tissue. It was found that CAT activity was lowest (p < 0.05) in the cauda epididymidis, whereas negligible GPx activity was detected in the reproductive tract tissues. There were no detectable differences in the mRNA expression level of Cu/Zn SOD among the different reproductive tract tissues. Small amounts of Ec‐SOD mRNA were found in the reproductive tract, particularly in the epididymides. The caput and cauda epididymides exhibited greater (p < 0.05) level of CAT mRNA expression, whereas PHGPx mRNA was more (p < 0.05) expressed in the testis. Furthermore, extremely large amounts of GPx5 mRNA were detected in the caput epididymidal tissue compared with other tissues of the reproductive tract. It can be suggested that the activity of the antioxidant enzymes and the relative gene expression of the enzymes confirm the presence of tissue‐specific antioxidant defence systems in the bison reproductive tract, which are required for spermatogenesis, epididymal maturation and storage of spermatozoa.